2018
DOI: 10.25179/tjem.20182202-p171
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Betatrophin with Fibroblast Growth Factor-21 in Women with Polycystic Ovary Syndrome

Abstract: Betatrophin and fibroblast growth factor-21 (FGF-21), as recently discovered members of hepatokine/adipokine family, have been proposed to be associated with some metabolic disorders in which insulin resistance plays a major role. We aimed to investigate serum betatrophin and FGF-21 concentrations in women with polycystic ovary syndrome (PCOS). In this cross-sectional study, we recruited 34 women with PCOS and 31 women as healthy controls. Serum betatrophin level and its relationship with serum FGF-21 level as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In PCOS patients, circulating ZAG levels were reported to be consistently reduced [10,27,28]. However, the relationship between circulating betatrophin levels and PCOS is controversial and the studies in the literature are inconsistent [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Growing evidence indicates that these cytokines have some roles in the pathogenesis of T2DM and PCOS, and are also involved in IR development.…”
Section: Discussionmentioning
confidence: 99%
“…In PCOS patients, circulating ZAG levels were reported to be consistently reduced [10,27,28]. However, the relationship between circulating betatrophin levels and PCOS is controversial and the studies in the literature are inconsistent [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Growing evidence indicates that these cytokines have some roles in the pathogenesis of T2DM and PCOS, and are also involved in IR development.…”
Section: Discussionmentioning
confidence: 99%
“…It's been reported that DCI-phosphoglycan and MI-phosphoglycan control key enzymes were involved in glucose and lipid metabolism [32,33]. β-trophin is a highly effective and specific pro-angiogenic factor, which acts through tyrosine kinase receptors to promote increased vascular permeability, extracellular matrix degeneration, and vascular endothelial cell migration [34,35]. In addition, elevated levels of androgen in patients with PCOS also lead to increased levels of β-trophin secreted by ovarian cells, which in turn exacerbates vascular proliferation in these patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…A strongly positive correlation was found between circulating betatrophin levels and LH, free-testosterone, HOMA-IR, BMI, insulin, FBG, and lipid profile (triglycerides, LDL-C, and total cholesterol) in both groups Calan et al [16]. Kahraman et al [17] suggested that betatrophin may participate in hormonal disturbances, especially LH alterations, in women with PCOS. The mechanism underlying the association between betatrophin and LH may be related to the signaling pathways between pituitary and liver, which may result in the stimulation of betatrophin by LH as a pituitary hormone.…”
Section: Fig 4 Correlation Between Betatrophin and Wisp1 Non-obese mentioning
confidence: 93%